Genetic influences on externalizing psychopathology overlap with cognitive functioning and show developmental variation. Issue 1 (31st March 2021) - Mollon, Josephine; Knowles, Emma E. M.; Mathias, Samuel R.; Rodrigue, Amanda; Moore, Tyler M.; Calkins, Monica E.; Gur, Ruben C.; Peralta, Juan Manuel; Weiner, Daniel J.; Robinson, Elise B.; Gur, Raquel E.; Blangero, John; et al.
Abstract: Background: Questions remain regarding whether genetic influences on early life psychopathology overlap with cognition and show developmental variation. Methods: Using data from 9, 421 individuals aged 8–21 from the Philadelphia Neurodevelopmental Cohort, factors of psychopathology were generated using a bifactor model of item-level data from a psychiatric interview. Five orthogonal factors were generated: anxious-misery (mood and anxiety), externalizing (attention deficit hyperactivity and conduct disorder), fear (phobias), psychosis-spectrum, and a general factor. Genetic analyses were conducted on a subsample of 4, 662 individuals of European American ancestry. A genetic relatedness matrix was used to estimate heritability of these factors, and genetic correlations with executive function, episodic memory, complex reasoning, social cognition, motor speed, and general cognitive ability. Gene × Age analyses determined whether genetic influences on these factors show developmental variation. Results: Externalizing was heritable ( h 2 = 0.46, p = 1 × 10 −6 ), but not anxious-misery ( h 2 = 0.09, p = 0.183), fear ( h 2 = 0.04, p = 0.337), psychosis-spectrum ( h 2 = 0.00, p = 0.494), or general psychopathology ( h 2 = 0.21, p = 0.040). Externalizing showed genetic overlap with face memory ( ρg = −0.412, p = 0.004), verbal reasoning ( ρg = −0.485, p = 0.001), spatial reasoning ( ρg = −0.426, p = 0.010), motor speed ( ρg = 0.659, p = 1x10 −4 ), verbal knowledge ( ρg = −0.314, p = 0.002), and general cognitive ability ( g) ( ρg = −0.394, p = 0.002). Gene × Age analyses revealed decreasing genetic variance ( γg = −0.146, p = 0.004) and increasing environmental variance ( γe = 0.059, p = 0.009) on externalizing. Conclusions: Cognitive impairment may be a useful endophenotype of externalizing psychopathology and, therefore, help elucidate its pathophysiological underpinnings. Decreasing genetic variance suggests that gene discovery efforts may be more fruitful in children than adolescents or young adults.